2020
DOI: 10.18231/j.jmra.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Basic protective measures against the new coronavirus pandemic– COVID-19

Abstract: Necessary steps to ensure that we are prepared well to face the challenge and threat posed by the growing pandemic of COVID-19 the Coronavirus with active support of the peoples of India. We have been able to contain the spread of the Virus in our country. The most important factor is preventing the spread of the virus locally is to empower the citizens with the right information and taking precaution as per the advisories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…The incubation period of COVID-19 plays a significant role in determining the suitable duration for quarantine measures and is essential for informing predictive models of incidence curves. However, it is noteworthy that several emerging studies have yielded diverse and varying results regarding the exact duration of this incubation period [47][48][49][50][51][52][53][54]. Lauer et al [55] examined publicly available data on 181 confirmed COVID-19 cases from China.…”
Section: Fuzzy Logic Model Developmentmentioning
confidence: 99%
“…The incubation period of COVID-19 plays a significant role in determining the suitable duration for quarantine measures and is essential for informing predictive models of incidence curves. However, it is noteworthy that several emerging studies have yielded diverse and varying results regarding the exact duration of this incubation period [47][48][49][50][51][52][53][54]. Lauer et al [55] examined publicly available data on 181 confirmed COVID-19 cases from China.…”
Section: Fuzzy Logic Model Developmentmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19) pandemic pushed all the governments around the world to take radical preventive measures to limit the rapid spread of the disease [1]. In light of the absence of effective antiviral treatment or sufficient vaccination at the beginning of the pandemic, the strategy adopted by the governments was concentrated on measures that limited social contact.…”
Section: Introductionmentioning
confidence: 99%
“…These measures included-but were not limited to isolating confirmed affected cases and tracing quarantine of their close contacts. Avoiding crowds in closed and/or poorly ventilated areas was also adopted for the public leading to the lockdown of schools and universities and the transition to distance learning [1]. These preventive measures led to a negative psychological impact on the public which was exaggerated by the misinformation about COVID-19 updates that were disseminated through social media.…”
Section: Introductionmentioning
confidence: 99%
“…Such measures showed a positive short-term positive on the environment such as decrease in atmospheric pollutants, reduction in carbon footprint, and decreased demand for fossil and petroleum fuels (due to restriction on traveling and industrial productions). Substantial reductions in environmental emission indices such as carbon, NO2, ozone (O3), SO2 , particulate matter (PM)2.5 and (PM)10 were recorded in major cities, around the globe [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%